2000
DOI: 10.1128/jvi.74.23.11121-11128.2000
|View full text |Cite
|
Sign up to set email alerts
|

Template Requirements for RNA Synthesis by a Recombinant Hepatitis C Virus RNA-Dependent RNA Polymerase

Abstract: The RNA-dependent RNA polymerase (RdRp) from hepatitis C virus (HCV), nonstructural protein 5B (NS5B), has recently been shown to direct de novo initiation using a number of complex RNA templates. In this study, we analyzed the features in simple RNA templates that are required to direct de novo initiation of RNA synthesis by HCV NS5B. NS5B was found to protect RNA fragments of 8 to 10 nucleotides (nt) from RNase digestion. However, NS5B could not direct RNA synthesis unless the template contained a stable sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
126
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 45 publications
7
126
1
Order By: Relevance
“…Like poliovirus (15), the HCV RdRp is capable of initiating viral RNA synthesis in vitro by a primer-dependent mechanism (9,10,16). However, Flaviviridae RdRps have also been shown to initiate RNA synthesis by a de novo mechanism (12,13,(17)(18)(19). De novo initiation of virus replication is the likely preferred mechanism for HCV in infected cells (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Like poliovirus (15), the HCV RdRp is capable of initiating viral RNA synthesis in vitro by a primer-dependent mechanism (9,10,16). However, Flaviviridae RdRps have also been shown to initiate RNA synthesis by a de novo mechanism (12,13,(17)(18)(19). De novo initiation of virus replication is the likely preferred mechanism for HCV in infected cells (20,21).…”
mentioning
confidence: 99%
“…RdRp initiates RNA synthesis preferentially from the 3Ј terminus of the template RNA (12)(13)(14), although in vitro it has been shown to lack specificity for viral RNA because it readily utilizes heterologous nonviral templates (9). Like poliovirus (15), the HCV RdRp is capable of initiating viral RNA synthesis in vitro by a primer-dependent mechanism (9,10,16).…”
mentioning
confidence: 99%
“…Initial cis cleavage through NS2-NS3 releases the NS3 protein, which in turn continues to process the precursor. Promising compounds with the ability to inhibit the viral protease (NS3) and the polymerase (NS5B) have been identified.NS5B is a 65-kDa RNA-dependent RNA polymerase capable of initiating RNA synthesis de novo in the absence of a primer (16,17,25,27,45). Three classes of inhibitors of HCV NS5B have been developed, namely, nucleoside analogue inhibitors, nonnucleoside analogue inhibitors, and pyrophosphate (PP i ) analogues.…”
mentioning
confidence: 99%
“…Inhibition of HCV NS5B in Primer-independent (de Novo) RdRp Assay-It was previously demonstrated that HCV NS5B can initiate the RNA synthesis utilizing the de novo mechanism (41)(42)(43). Using the full-length ϳ9500-nucleotide HCV subgenomic replicon RNA template, we examined the effect of mAbs in de novo RdRp assays.…”
Section: Resultsmentioning
confidence: 99%
“…Because the copy-back or self-priming RNA synthesis by itself is incapable of generating the precise viral genome 5Ј and 3Ј termini, de novo initiation of viral replication is the most likely mechanism for HCV in infected cells (41,48,49). Moreover, in cells harboring HCV subgenomic replicons (e.g.…”
Section: Mab 7g8 Epitope Amino Acid Residues Are Involved In the Intementioning
confidence: 99%